Effect of provider-initiated testing and counselling and integration of ART services on access to HIV diagnosis and treatment for children in Lilongwe, Malawi: a pre- post comparison - Phiri Sam; Mwansambo Charles; Kamthunzi Portia; Weigel Ralf; Kazembe Peter N (BMC, 2009)
Abstract Background The HIV prevalence in Malawi is 12% and Kamuzu Central Hospital (KCH), in the capital Lilongwe, is the main provider of adult and paediatric HIV services in the central region. The Lighthouse at KCH offers opt-in HIV testing and counselling (HTC) for adults and children. In June 2004, Lighthouse was the first clinic to provide free antiretroviral treatment (ART) in the public sector, but few children accessed the services. In response, provider-initiated HIV testing and counselling (PITC) and an ART clinic were introduced at the paediatric department at KCH in Quarter 4 (Q4) 2004. Methods We analysed prospectively collected, aggregated data of quarterly reports from Q1 2003 to Q4 2006 from HTC centre registers, ART registers and clinic registrations at the ART clinics of both Lighthouse and the paediatric department. By comparing data of both facilities before (Q1 2003 to Q3 2004), and after the introduction of the services at the paediatric department (Q4 2004 to Q4 2006), we assessed the effect of this intervention on the uptake of HIV services for children at KCH. Results Overall, 3971 children were tested for HIV, 2428 HIV-infected children were registered for care and 1218 started ART. Between the two periods, the median (IQR) number of children being tested, registered and starting ART per quarter rose from 101 (53-109) to 358 (318-440), 56 (50-82) to 226 (192-234) and 18 (8-23) to 139 (115-150), respectively. The median proportion of tested clients per quarter that were children rose from 3.8% (2.7-4.3) to 9.6% (8.8 to 10.0) (p = 0.0009) and the proportion of ART starters that were children rose from 6.9% (4.9-9.3) to 21.1% (19.2-24.2) (p = 0.0036). The proportion of registered children and adults starting ART each quarter increased similarly, from 26% to 53%, and 20% to 52%, respectively. Conclusions Implementation of PITC and integration of ART services within the paediatric ward are likely to be the main reasons for improved access to HTC and ART for children at KCH, and can be recommended to other hospitals with paediatric inpatients in resource limited settings with high HIV prevalence.